Cu2O@nanoporous carbon composites derived from Cu-based MOFs with ultrabroad-bandwidth electromagnetic wave absorbing performance. Issue 2 (15th January 2021) - Yang, Huili; Zhang, Xiang; Xiong, Zhiqiang; Shen, Zhongjing; Liu, Chongbo; Xie, Yu
Abstract: The application of carbon-based materials in microwave absorption (MA) field are limited due to the impedance mismatch caused by high permittivity and low permeability. In this work, Cu2 O@nanoporous carbon (Cu2 O@NPC) composites derived from Cu-based MOFs are synthesized using a simple method. Variation of C and Cu2 O contents in Cu2 O@NPC allows the regulation of permittivity and permeability, resulting in superior ultrabroad-bandwidth absorptivity. The maximum reflection loss (RL) of Cu2 O@NPC-4 is up to −31.1 dB at 5.6 GHz, while the effective bandwidth (RL ≤ −10 dB) can reach 7.3 GHz (10.7–18 GHz) with a matching thickness of 1.85 mm. The results of this study open a new opportunity for solving the impedance mismatch of C-based materials and obtain ultrabroad effective bandwidth.